Unidirectional multilingual convergence: typological and social factors - Yakpo, Kofi (International journal of multilingualism, 2023)
Suriname represents an interesting case of unidirectional multilingual convergence in a linguistic area. The multilingual ecology of Suriname is hierarchical. The Germanic language Dutch exerts structural and lexical influence 'downwards', but other languages do not do so 'upwards' to the same degree. This study analyses the development of word order in the Indo-Aryan language Sarnami and the Afro-Caribbean English-lexifier Creole Sranan, the two largest languages of Suriname besides Dutch. The results show that Sarnami and Sranan have undergone a typological realignment in word order. Sranan has completed a shift from postpositional locative nouns to prepositions through language contact and structural borrowing from Dutch. Sarnami is acquiring SVO (Subject-Verb-Object) as a basic word order next to SOV (Subject-Object-Verb) through structural borrowing from Dutch and Sranan. Conversely, standardisation pressures prevent innovative linguistic practices and structural borrowing from the other languages of Suriname from consolidating themselves in Surinamese Dutch in a similar way. The change that spoken Dutch has undergone in Suriname through influence from Sranan and Sarnami is therefore more modest than the changes Sranan and Sarnami have incurred through Surinamese Dutch influence. This study compares changes in these three languages for the first time and highlights the role of both social and typological factors in driving or impeding areal convergence in multilingual ecologies.